Bothrops alternatus Snake Venom Induces Cytokine Expression and Oxidative Stress on Renal Function - Nogueira Junior, F. A.; Coelho Jorge, A. R.; Marinho, A. D.; Moraes Silveira, J. A. de; Queiroz Alves, N. T.; Sa Costa, P. H.; Braga E Silva, P. L.; Maia Chaves-Filho, A. J.; Lima, D. B.; Sampaio, T. L.; Morais, G. B. de; Azul Monteiro Evangelista, J. S.; et al. (Bentham Science Publ Ltd, 2019)
Background: Envenomation caused by Bothrops alternatus is common in Southern Brazil. Acute Kidney Injury occurs after Bothrops snakebite and more information is necessaryrequired to understand its mechanism. Objective: The objective was to evaluate the effect of Bothrops alternatus venom (BaV) on renal cells and rat isolated kidney function. Methods: Wistar rats (n = 6, weighing 260-320 g) were perfused with a Krebs-Henseleit solution containing 6 g 100 mL(-1) of bovine serum albumin. After 30 minutes, the kidneys were perfused with BaV to a final concentration of 1 and 3 mu gmL(-1); and subsequently were evaluated for Perfusion Pressure (PP), Renal Vascular Resistance (RVR), Urinary Flow (UF), Glomerular Filtration Rate (GFR), and percentage of electrolyte tubular transport. Renal histological analysis, cytokine release, oxidative stress and cytotoxicity in renal proximal tubular cells were assessed. Results: BaV reduced PP, RVR, GFR, UF, total and proximal sodium transport (% TNa+), and chloride (%TCl-) in the isolated kidney perfusion model. Histological analysis of perfused kidneys disclosed the presence of proteinaceous material in the glomeruli and renal tubules, vacuolar tubular epithelial cell degeneration, Bowman's capsule degeneration, swelling of glomerular epithelial cells, glomerular atrophy and degeneration, and the presence of intratubular protein. Cytokine release (TNF-alpha, IL-1 beta, IL-10) and oxidative stress were increased in the kidneys. The viability of LLC-MK2 cells (IC50: 221.3 mu g/mL) was decreased by BaV and necrosis was involved in cell death. Conclusion: These findings indicate that BaV modifies functional parameters in an isolated perfused kidney model and has cytotoxic effects on renal lineage cells.
Keywords: Snake envenomation; Bothrops alternatus; Kidney perfusion; Cytotoxicity; Necrosis; Acute kidney injury